The Difference in Obesity Between Adults and Elderly with Knee Osteoarthritis - Pradigo, Raynald; Tarigan, Ricky (Clinical and Research Journal in Internal Medicine, 2023)
Background: Knee osteoarthritis (KOA) is one of the most common diseases of arthritis. The increase in KOA prevalence is also affected by the increase in obesity prevalence as one of the KOA risk factors. Aim: To see the difference in obesity association with KOA between adults and the elderly. Methods: The study design is analytic cross-sectional. 102 cases and controls data each are collected from Tarempa public health center (Phc) medical records by simple random sampling using a random number generator. Data taken is the latest patient visit record in the form of name, age, gender, weight, and height. Data are then analyzed using SPSS. This study's ethical clearance is accepted by the ethic committee faculty of medicine University of Sumatera Utara. Results: 59 (28.9%) men and 83 (71.1%) women participated in this study. The mean age of KOA subjects is 57.5 ± 11,4 with the most age range being 50-59 years old (38.2%). 71 (69.6%) KOA subjects are obese. The results of data analysis show that people ≥ 50 y.o with obesity were at 2.7 times more risk of suffering KOA than the normoweight or overweight people. There is no association between obesity and KOA in people under 50 years old. Conclusion: The risk of obesity developing into knee OA increased with age